The timing of guilty pleas : lessons from common law jurisdictions / Kevin Kwok-yin Cheng, The Chinese University of Hong Kong. - Cheng, Kevin Kwok-yin, 1985- (Cambridge University Press, 2023)
While guilty pleas are the primary mode of criminal case dispositions across different legal jurisdictions, this topic remains an understudied area. The assumption is that defendants are 'playing the system' and that a sliding scale of sentence discounts is necessary to encourage early guilty pleas, which offer utilitarian benefits of efficiency. These assumptions lack a solid empirical foundation. This book offers a comprehensive investigation of how the timing of guilty pleas affects various facets of the criminal process, from the factors that affect this timing, to the effects that the sliding scale of sentence discounts have on sentences and public opinions about them. It also draws comparisons between Western and Asian legal systems, specifically those of England and Wales and Hong Kong. This book is addressed to scholars, legal practitioners, policymakers and those interested in criminal justice, socio-legal studies and empirical legal research.